Dealloying Synthesis of Silicon Nanotubes for High‐Performance Lithium Ion Batteries. Issue 9 (4th May 2022) - Zhao, Jinfu; Wei, Wenxian; Xu, Na; Wang, Xiaotong; Chang, Limin; Wang, Li; Fang, Luan; Le, Zaiyuan; Nie, Ping
Abstract: The front cover artwork is provided by Dr. Ping Nie and Prof. Limin Chang at Jilin Normal University. The image shows one‐dimensional silicon–nitrogen‐doped carbon nanotube composite fabricated through a dealloying process. The nanotube engineered silicon coupled with conductive carbon coating synergistically boosts the electrochemical performance. Read the full text of the Research Article at 10.1002/cphc.202100832 . Abstract : "One dimensional tubular silicon–carbon composites are delicately designed by a simple dealloying method using Mg2 Si and biopolymer polydopamine as precursors. The full battery assembled with the as‐prepared anode material and commercial LiFePO4 cathode exhibits high energy density and good cycling stability…" This and more about the story behind the front cover can be found in the Research Article at 10.1002/cphc.202100832 .